MIMO Antenna Array Design with Polynomial Factorization - Wen-Qin Wang; Huaizong Shao; Jingye Cai (International Journal of Antennas and Propagation)
One of the main advantages of multiple-input multiple-output (MIMO) antenna is that the degrees-of-freedom can be significantly increased by the concept of virtual antenna array, and thus the MIMO antenna array should be carefully designed to fully utilize the virtual antenna array. In this paper, we design the MIMO antenna array with the polynomial factorization method. For a desired virtual antenna array, the polynomial factorization method can optimally design the specified MIMO transmitter and receiver. The array performance is examined by analyzing the degrees-of-freedom and statistical output signal-to-interference-plus-noise ratio (SINR) performance. Design examples and simulation results are provided.